2016
DOI: 10.1021/acs.organomet.6b00003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Pincer-Ligated Palladium-Catalyzed Arylation of Azoles with Aryl Iodides: Evidence of a PdII–PdIV–PdII Pathway

Abstract: Pincer-based ( R2 POCN R ′ 2 )PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient ( iPr2 POCN Et2 )PdCl (2a) catalyst, which emphasizes a rare Pd II −Pd IV −Pd II redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C−H bond cleavage on azoles occurs via tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 101 publications
1
16
0
Order By: Relevance
“…Our results are in fact similar, for example, to those very recently reported for the direct arylation of azoles in the presence of a pincer-ligated palladium complex. 16 In that study, the high reactivity observed when electron-rich aryl halides are the coupling partners was attributed to a better stabilization of Pd(IV) intermediates resulting from the oxidative addition of the aryl halide to a Pd(II) species. a Method A: 1) 2 (1.0 mmol), 3 (3.0 equiv), Pd(OAc) 2 (5 mol%), CsOAc (2.0 equiv), DMA (5 mL), 110 °C, 24 h; 2) CuI (2.0 equiv), 140 °C, 24 h. Method B: (1.0 mmol), 3 (3.0 equiv), Pd(OAc) 2 (5 mol%), P(2-furyl) 3 (10 mol%), K 2 CO 3 (2.0 equiv), xylene (5 mL), 140 °C, 24 h. b Isolated yield.…”
Section: Special Topic Syn Thesismentioning
confidence: 93%
See 1 more Smart Citation
“…Our results are in fact similar, for example, to those very recently reported for the direct arylation of azoles in the presence of a pincer-ligated palladium complex. 16 In that study, the high reactivity observed when electron-rich aryl halides are the coupling partners was attributed to a better stabilization of Pd(IV) intermediates resulting from the oxidative addition of the aryl halide to a Pd(II) species. a Method A: 1) 2 (1.0 mmol), 3 (3.0 equiv), Pd(OAc) 2 (5 mol%), CsOAc (2.0 equiv), DMA (5 mL), 110 °C, 24 h; 2) CuI (2.0 equiv), 140 °C, 24 h. Method B: (1.0 mmol), 3 (3.0 equiv), Pd(OAc) 2 (5 mol%), P(2-furyl) 3 (10 mol%), K 2 CO 3 (2.0 equiv), xylene (5 mL), 140 °C, 24 h. b Isolated yield.…”
Section: Special Topic Syn Thesismentioning
confidence: 93%
“…Regarding electron-rich aryl bromides, the results using Method A were not completely satisfactory. The reaction of 4-bromotoluene (3l), 3-bromotoluene (3m), 2-bromotoluene (3n), and 4-bromoanisole (3o) gave the 2,5-diarylimidazoles 4l, 4m, 4n, and 4o, in 49%, 47%, 23%, and 33% isolated yield, respectively (Table 2, entries 12 and [14][15][16].…”
Section: Special Topic Syn Thesismentioning
confidence: 99%
“…of iodobenzene in 1,4-dioxane at 140 • C for 16 h. The reaction led to a massive decomposition of the complex together with a small amount of the expected coupling product (<15% of the identified species) as inferred from the 1 H NMR analysis of the crude reaction mixture that shows a very complex mixture. This illustrates the less stable (or more reactive) character of the Cp* derivative 8, when compared to its Cp analogue 7, and suggests the possible involvement of such a benzothiazolyl complex in the coupling reaction [23,[39][40][41], provided that it does not constitute a potential energy well like the Cp derivative 7.…”
Section: Investigation Of the Reactivity Of The Cp* Complexmentioning
confidence: 95%
“…Interestingly, although C(2)-benzoxazolyl or benzothiazolyl complexes are often proposed as intermediates in C-H/C-X couplings between heteroarenes and aryl, alkenyl or alkyl electrophiles [5,10,12,14,16,17,19,20,22,23], they remain very rare. We are indeed aware of only four related PCN-Pd [39][40][41] and NNN-Ni [23] pincer species, which have been isolated with a benzothiazolyl ligand and demonstrated to be intermediates in similar couplings. Thus, although it obviously constitutes a potential energy well, complex 7 is an interesting example of azolyl trapping in such (attempted) direct coupling.…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…Surprisingly, PEPPSI themed palladium precatalysts for the arylation of benzothiazole unit with aryl halides were not reported till date, whereas the arylation of other heterocyclic compounds like imidazoles, 2‐substituted thiophene derivatives, and 1‐methylpyrrole‐2‐carboxaldehyde with aryl halides have been studied extensively 2n, p, 13. Furthermore, mechanistic details of palladium catalyzed arylation of benzothiazoles by Punji and co‐workers revealed the importance of σ‐donor ligands on palladium center, which will enhance the oxidative addition of aryl halide electrophiles and stabilized the Pd (IV) intermediate . Based on the above findings we have explored the catalytic activity of our palladium complexes (having strong σ‐donor ligands such as N‐heterocyclic carbene) for C‐H bond arylation of benzothiazole at low catalyst loading.…”
Section: Introductionmentioning
confidence: 99%